Securing Zero Black Liquor Discharge in Pulp and Paper Industries of River Ganga Basin through Participatory Approach - Singh, R. K.; Vidyarthi, A.K.; Shukla, A.; Ranjan, P.; Kumar, V.; Kumar, R. (Indian Forester, 2023)
The pulp and paper industry has been considered a large consumer of freshwater and one of the largest sources of surface water pollution. The Indian paper industry are highly intensive in terms of consumption of raw material, chemicals, energy, and water thereby generating high volume of wastewater with complex characteristics, black liquor with high Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Total Suspended Solids (TSS). Central Pollution Control Board (CPCB), after consultation with different stakeholders prepared an action plan for black liquor management in Pulp and Paper industries. The action plan was successfully Implemented and resulted into zero black liquor discharge In river Ganga basin since 2014. To ensure zero black liquor discharge, around 100 chemical pulping digesters were dismantled, and 7 Chemical Recovery Plants (CRP) were commissioned for black liquor management. The initiatives and ensurance of zero black liquor discharge from Pulp and Paper Industry in Uttarakhand and Uttar Pradesh was acknowledged by Hon’ble Prime Minister of India in Mann ki Baat, Episode-19th dated 24/04/2016. The Pulp and Paper industries located in Ganga basin are being inspected annually with technology partners for verification and to ensure no black liquor discharge into recipient water bodies. Implementation of zero black liquor discharge led to improvement in water quality of recipient water bodies such as river Dhela, Bahela, Kosiand Ramgangain terms of Dissolved Oxygen (DO) and Bio-chemical Oxygen Demand (BOD) and no incidence of coloured water discharge observed in river Ganga since 2017. Implementation of action plan and continuous surveillance through annual inspection of pulp and paper industries led to reduction in pollution load from 76.5 TPD to 1.74 TPD in 2021 as compared to 2011. The successful case of this holistic participatory approach and policy needs to be Implemented nationwide for black liquor management in Pulp and Paper mills.